A Is For Alphabet... Roman Letters And Their Use In Written English - B. Dickerson, Wayne (Penerbit Universiti Sains Malaysia, 2006)
The Roman alphabet is so omnipresent we hardly notice it. Yet it is one of man's greatest inventions. Where did its peculiar shapes come from? Why are they arranged with uppercase and lowercase letters distributed left to right on a horizontal line with spaces and punctuation marks? This article traces the 4000-year-old history of the alphabet to its current manifestation in English writing. We also address this question: How do these shapes do their job of representing language? Answer: With more regularity than we often appreciate. Particularly for learners of English, the regularities may offer some valuable insights into the principled ways we use the alphabet; order is everywhere. Furthermore, by learning how the oddities in our spelling arose, we may come to view them less as bothersome idiosyncrasies and more as interesting historical markers left by the amazing trek our alphabet has taken across time, space and through a myriad languages.